2011
DOI: 10.1128/jb.01335-10
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Salmonella enterica Serovar TyphimuriumydcIGene, Which Encodes a Conserved DNA Binding Protein Required for Full Acid Stress Resistance

Abstract: Salmonella enterica serovar Typhimurium possesses a stimulon of genes that are differentially regulated in response to conditions of low fluid shear force that increase bacterial virulence and alter other phenotypes. In this study, we show that a previously uncharacterized member of this stimulon, ydcI or STM1625, encodes a highly conserved DNA binding protein with related homologs present in a range of Gram-negative bacterial genera. Gene expression analysis shows that ydcI is expressed in different bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…Previous studies showed that YdcI is responsible for acid stress and oxidative stress in Salmonella enterica (55) . We analyzed the protein identity of YdcI among multiple strains across Gram-negative bacteria and found that YdcI is a highly and broadly conserved protein ( Figure 5A).…”
Section: Case Ii: Ydci Is a Transcription Factor Involved In Proton Amentioning
confidence: 99%
“…Previous studies showed that YdcI is responsible for acid stress and oxidative stress in Salmonella enterica (55) . We analyzed the protein identity of YdcI among multiple strains across Gram-negative bacteria and found that YdcI is a highly and broadly conserved protein ( Figure 5A).…”
Section: Case Ii: Ydci Is a Transcription Factor Involved In Proton Amentioning
confidence: 99%
“…Genes encoding the secretion apparatus of SPI‐2 and motility genes were found to be more transcribed in presence of sprouts. The gene ydcI (SENTW_1576) encoding a conserved DNA‐binding protein is related to stress resistance, and possibly, virulence (Jennings et al ., ) was more transcribed in presence of sprouts. Additional higher transcribed genes in presence of sprouts encode the regulator RcsA (SENTW_1101), which is besides RcsB one of the positive regulators for transcription of capsular polysaccharide synthesis in E. coli (Sledjeski and Gottesman, ) and YdhM (SENTW_1780), which is a putative TetR‐family regulator that mainly regulates biosynthesis of antibiotics, efflux pumps and osmotic stress (Ramos et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Lozada-Chávez et al [40] analyzed the gene-regulatory network structure using a largescale data set, and proposed that the gene-network hierarchy consists of global and local regulators, as seen in the relationships between E. coli ArcA and YdcI and B. subtilis CcpA and CcpC. Genome-sequence data revealed that E. coli ArcA was well-conserved and E. coli YdcI was partially conserved among γ-proteobacteria [41], whereas the ydcI gene was suggested to be acquired after divergence by gene duplication [40]. The TCA cycle local regulatory system in E. coli is suggested to have evolved in a biologically appropriate manner.…”
Section: Discussionmentioning
confidence: 99%